Atopic dermatitis: Update on comorbidities and therapeutic advances - Katie Kim; Caitlin Crimp; Robert Sidbury (Wolters Kluwer Medknow Publications, 2019)
Atopic dermatitis (AD) is a chronic inflammatory disorder that primarily affects the skin. Recent literature has expanded our knowledge of associated comorbidities. In this review, we will discuss sleep loss, attention deficit hyperactivity disorder, obesity, and anemia as they relate to AD. We will also review two recently approved medications and how they fit into the therapeutic ladder.